2023
DOI: 10.1002/cbdv.202200523
|View full text |Cite
|
Sign up to set email alerts
|

Chamomile Essential Oil: Chemical Constituents and Antitumor Activity in MDA‐MB‐231 Cells through PI3K/Akt/mTOR Signaling Pathway

Abstract: Chamomile essential oil (CEO) is extracted from chamomile and mainly used in aromatherapy. The chemical constituents and its antitumor activity on Triple-negative breast cancer (TNBC) was explored in the present study. Gas chromatography-mass spectrometry (GC/MS) was employed to analyze the chemical constituents of CEO. The cell viability, migration and invasion of TNBC cell MDA-MB-231 were measured using MTT, wound scratch and Transwell assay, respectively. The protein expression of PI3K/Akt/mTOR signaling pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 50 publications
0
3
0
Order By: Relevance
“…Furthermore, a recent study showed that chamomile EO derived from Matricaria recutita L. effectively inhibited the growth, migration, and invasion of MDA-MB-231 cells, even at concentrations as low as 1-2 μg/mL. Notably, this EO inhibited the phosphorylation of PI3K, Akt, and mTOR, and blocked the activation of the PI3K/Akt/ mTOR signaling axis to exert these anticancer effects (An et al, 2023). proportion of splenic T helper (CD3 + , CD4 + ) and T cytotoxic (CD3 + , CD8 + ) cells, resulting in cycle arrest at the G0/G1 phase and inhibition of tumor growth in in vivo (Morsi et al, 2022).…”
Section: Anticancer Activities Of Eos In In Vitro Bc Modelsmentioning
confidence: 96%
“…Furthermore, a recent study showed that chamomile EO derived from Matricaria recutita L. effectively inhibited the growth, migration, and invasion of MDA-MB-231 cells, even at concentrations as low as 1-2 μg/mL. Notably, this EO inhibited the phosphorylation of PI3K, Akt, and mTOR, and blocked the activation of the PI3K/Akt/ mTOR signaling axis to exert these anticancer effects (An et al, 2023). proportion of splenic T helper (CD3 + , CD4 + ) and T cytotoxic (CD3 + , CD8 + ) cells, resulting in cycle arrest at the G0/G1 phase and inhibition of tumor growth in in vivo (Morsi et al, 2022).…”
Section: Anticancer Activities Of Eos In In Vitro Bc Modelsmentioning
confidence: 96%
“…In addition, chamomile EOs reduced the migration and invasion of MDA-MB-231 cells. Based on these findings, it was suggested that the cytotoxic effects of chamomile EOs were due to the inhibition of PI3K/Akt/mTOR signalling pathway in MDA-MB-231 cells [ 53 ]. Overall, the demonstrated biological activity might be primarily attributed to the volatile constituents present in the EOs.…”
Section: Essential Oils (Eos)mentioning
confidence: 99%
“…Natural products or their derivatives represent more than 60% of the molecules used for cancer treatment [6]. In this context, essential oils (EOs) have been widely investigated for their pharmacological effects, including antimicrobial [7,8], anti-inflammatory [9], and antitumor effects [10][11][12][13][14][15]. EOs are aromatic oily liquids obtained from many parts of plants such as flowers, seeds, leaves, twigs, and roots.…”
Section: Introductionmentioning
confidence: 99%